2021
DOI: 10.1007/s00253-021-11364-1
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of mouse monoclonal antibodies targeting to distinct epitopes of Zika virus envelope protein for specific detection of Zika virus

Abstract: The recent Zika virus (ZIKV) epidemic poses a serious threat to global health due to its association with microcephaly and congenital diseases in newborns and neurological complications and Guillain-Barré syndrome in adults. However, the majority of people infected with ZIKV do not develop symptoms. The platforms aimed to specifically diagnose ZIKV infection are needed for patient care and public health surveillance. In the study, four ZIKV envelope (E) protein-specific monoclonal antibodies (mAbs) (A1, B1, C1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Though it is not clear whether co-infected patients develop more severe disease [ 39 42 ], increased co-circulation and transmission of multiple flaviviruses will surely pose significant problems for diagnosis and surveillance because of the common clinical presentation, asymptomatic response, and cross-reactivity. Although progress is being made on the diagnostics front [ 43 45 ], effective vector control remains the most effective approach to managing and eliminating mosquito-borne diseases [ 3 ]. Central to vector control is a clear understanding of the pathogen-vector relationship as it evolves in real-time, with expanding arboviral co-circulation being a worrying trend that we have addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Though it is not clear whether co-infected patients develop more severe disease [ 39 42 ], increased co-circulation and transmission of multiple flaviviruses will surely pose significant problems for diagnosis and surveillance because of the common clinical presentation, asymptomatic response, and cross-reactivity. Although progress is being made on the diagnostics front [ 43 45 ], effective vector control remains the most effective approach to managing and eliminating mosquito-borne diseases [ 3 ]. Central to vector control is a clear understanding of the pathogen-vector relationship as it evolves in real-time, with expanding arboviral co-circulation being a worrying trend that we have addressed.…”
Section: Discussionmentioning
confidence: 99%
“…2A , viii). To be noted, S2-10H showed no inhibition of syncytium, like the isotype control antibody ZIKV-A1 ( 30 ) ( Fig. 2A , iii and iv).…”
Section: Resultsmentioning
confidence: 82%
“…The pseudotyped lentivirus containing with the cell-surface expressed SARS-CoV-2 S protein and the internal EGFP or luciferase reporter gene was utilized to examine whether 7 Eb-4G and 1Ba–3H can inhibit the pseudotyped virus infection in ACE2-293T cells. The results showed that the isotype control antibody ZIKV-B1( Li et al, 2021 ) and 7 Eb-4G did not have any neutralizing activity since the EGFP was successfully expressed upon pseudotyped virus infection in ACE2-293T cells ( Fig. 3 A).…”
Section: Resultsmentioning
confidence: 99%